Gender differences in the clinical course of Finnish gelsolin amyloidosis. (2nd January 2016) - Atula, Sari; Nikoskinen, Tuuli; Saastamoinen, Aleksi; Strbian, Daniel; Schmidt, Eeva-Kaisa; Kiuru-Enari, Sari
Abstract: Purpose : To investigate gender differences in Finnish gelsolin amyloidosis (AGel amyloidosis). Patients and methods : AGel amyloidosis patients, who were members of Finnish Amyloidosis Association (SAMY), filled in a questionnaire compiling known and suspected aspects of their disease. Telephone interviews and hospital medical records, when available, complemented the questionnaire. The data were entered to the database in order to create a national AGel amyloidosis patient registry (FIN-GAR). Results : A total of 227 patients, 156 women and 71 men, participated in the study. The women in our registry noticed their first symptoms at the median age of 39 years versus 43 years for men ( p = 0.01). At the age in which the diagnosis was made there was a trend to be observed between men and women (women: 39 years versus men: 43 years, p = 0.053). Corneal lattice dystrophy was diagnosed in significantly younger women than men (median ages 41 versus 49 years, respectively, p = 0.01). Of other ophthalmological manifestations, corneal ulcer, impaired vision and glaucoma were all diagnosed at least 5 years earlier in women, although differences were not statistically significant. Ophthalmological manifestations, such as dry eyes and corneal ulcer; dermatological signs, such as blepharochalasis, and also neurological symptoms, such as myokymia and carpal tunnel syndrome, were more prevalent among women. Conclusions : In the largest so far available study on AGel amyloidosis we show that women developed symptoms and signs of AGel amyloidosis at younger age. Especially eye-related problems occurred earlier and together with nerve and skin manifestations, the characteristic clinical triad in AGel amyloidosis, were more common in women. However, a clear limitation of our study was a selection bias caused by a significant underrepresentation of men in the study population.